AKTIVITAS ANTIOKSIDAN DAN ANTIBAKTERI EKSTRAK DAUN Strobilanthes crispus Bl (Keji Beling) ) TERHADAP Staphylococcus aureus DAN Escherichia coli - Sukaina Adibi; Hendry Nordan; Septri Nurjaya Ningsih; Moga Kurnia; Evando Evando; Salastri Rohiat (University of Bengkulu, 2017)
[ANTIXOXIDANT AND ANTIBACTERIA ACTIVITIES OF Strobilanthes crispus Bl (Keji Beling) EXTRACT AGAINST Stapylococcus Aureus AND Escherichia coli] Strobilanthes crispus Bl (Keji Beling) is one of herbs that has been used for the treatment of several types of diseases such as kidney stones, gall stones, diabetes, cholesterol, tumors and others. The purpose of this study was to determine the value of antioxidant activity (IC50) and antibacterial activity of ethanol extract of leaf vermicelli against Staphylococcus aureus and Escherichia coli bacteria. Antioxidant test was performed using DPPH method and vitamin C was used as standard. While the antibacterial activity test done by paper disc method. Amphicillin is used as a positive control and aquades as a negative control. Ethanol extract of leaf vermicelli able to counteract free radical of DPPH with IC50 value that is: 102.85 ppm and IC50 value from vitamin C as comparative solution equal to 19.268 ppm. The results of antibacterial inhibition test of ethanol extract of vile leaf on S. aureus bacteria with extract concentration of 20% (0 mm), 40% (2.5 mm), 60% (3.25 mm), and 80% (4.75) were included Weak and 100% (5.75 mm) including Medium, and E.coli antibacterial inhibition in the extract con- tacts of 20% (0 mm), 40% (2 mm), 60% (2.25 mm), 80% (4.25 mm) were weak, and 100% (5.25 mm ) including moderate. So it is known that the extract of ethanol leaves vile at 100% concentration can inhibit the growth of S. aureus bacteria and E. coli bacteria characterized by the formation of the largest clear zone diameter at the concentration. But the strength of its bacteria is still not effective to inhibit the growth of both test bacteria.